Results from the event organized in Prague, with representatives of the project partners and the municipalities of the Baixo Alentejo region - Ramos, Mário (2022)
This report presents the results of a participatory workshop involving participants from Portugal, the Czech Republic, Norway, and Romania, aimed at presenting the main outcomes achieved within the EEA Grants project "(De)construct for Circular Economy" in Portugal. The workshop also provided an opportunity to exchange experiences and consider different contexts. This exchange was deemed crucial for understanding how the results from Portugal could be applied or adapted to other contexts and/or scales, and how the experiences from the other countries could contribute to improving Portuguese strategies. Additionally, the workshop was designed to bring together the executive representatives of the Baixo Alentejo region of Portugal and all project partners, with the goal of raising political awareness regarding decisions to be made about construction and demolition waste (CDW) management and the application of circular economy principles in the construction sector, at the regional and/or local level.